(Un)justified expectations on nuclear deterrence of non-nuclear NATO members: the case of Estonia and Latvia?. Issue 3 (3rd July 2018) - Veebel, Viljar
ABSTRACT: Nuclear assets are one of the cornerstones of credible collective deterrence of the North Atlantic Treaty Organisation. Paradoxically, the most endangered member states are the ones without nuclear capabilities, left with the hope and expectation that the owners of nuclear assets will defend them and that their potential enemies are deterred by these capabilities. However, the expectations from one side, practical commitment of allies from other side may not go in harmony and synchronisation. Is there a capability gap which needs to be fulfilled? If yes then, is the gap in the side of nuclear powers or is it on the side of those endangered states who need to understand what can or cannot realistically be expected? The current article focuses on the question of how the political and military elite of the Baltic states describes their expectations in terms of using Alliance's nuclear capabilities to deter Russia's regional ambitions.